2020
DOI: 10.3389/fpls.2020.01209
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bt Protein in Transgenic Bt Cotton Plants and Ecological Fitness of These Plants in Different Habitats

Abstract: Fitness is one of the key parameters to evaluate the effects of transgenic plants on the ecological environment. To evaluate the ecological risk of transgenic Bt cotton plants growing in different habitats, we determined the expression of the exogenous Bt gene and the fitness of transgenic and non-transgenic cotton plants in three habitats (farmland, grassland, and shrub). We observed that the expression of Bt protein in the farmland was significantly higher than that in the natural habitat, and when the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…frugiperda calculated by Jin et al 46 . was based on a Vip3Aa concentration of 0.4 μg cm −2 , which is lower than the concentration typically produced by Bt corn and cotton plants 47–50 . Previous studies show that the degree of dominance varies based on Bt concentrations, with nonrecessive resistance at low concentration and more recessive resistance at high concentrations 23,51 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…frugiperda calculated by Jin et al 46 . was based on a Vip3Aa concentration of 0.4 μg cm −2 , which is lower than the concentration typically produced by Bt corn and cotton plants 47–50 . Previous studies show that the degree of dominance varies based on Bt concentrations, with nonrecessive resistance at low concentration and more recessive resistance at high concentrations 23,51 .…”
Section: Discussionmentioning
confidence: 95%
“…46 However, this degree of dominance in S. frugiperda calculated by Jin et al 46 was based on a Vip3Aa concentration of 0.4 μg cm −2 , which is lower than the concentration typically produced by Bt corn and cotton plants. [47][48][49][50] Previous studies show that the degree of dominance varies based on Bt concentrations, with nonrecessive resistance at low concentration and more recessive resistance at high concentrations. 23,51 Resistance to Vip3Aa in strains of Helicoverpa punctigera and Helicoverpa armigera from Australia also was monogenic and essentially recessive.…”
Section: Discussionmentioning
confidence: 99%
“…Bt cotton growing in different habitats (farmland, grassland and shrubs) were assessed for fitness level. It was found that the expression of Bt protein in the farmland was significantly higher than that in the other habitats (Liu et al, 2020).…”
Section: Bt Gene Expression Resistance Maintain and Lossesmentioning
confidence: 93%
“…Fitness is also one of the key parameters to evaluate the effects of transformed plants on the ecological environment (Liu et al, 2020). Bt cotton growing in different habitats (farmland, grassland and shrubs) were assessed for fitness level.…”
Section: Bt Gene Expression Resistance Maintain and Lossesmentioning
confidence: 99%
“…Each accession was grown in two 40 feet rows where individual plants were space planted with a 1-foot plant-to-plant and row-to-row distance. As stated, the experiment was performed at the same field location for three years to avoid, as much as possible, edaphic, management, and ecological variabilities (insect pest and pathogen pressure), as the gene expression traits were shown earlier to be highly influenced by these factors [ 86 ]. Three plants, specifically somewhat from the center of the two rows showing the characteristics of specific genotypes, were tagged and used for taking plant samples to serve as three biological replicates in the experiment.…”
Section: Methodsmentioning
confidence: 99%